Pengaruh Kualitas Pelayanan Dan Harga Terhadap Loyalitas Melalui Kepuasan Konsumen Toko Klontong Madura - Kusnadi, Kusnadi; Hidayati, Nur; Farida, Eka (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The retail sector, especially the Madura klotong shop, is experiencing very significant development. This shop is known as a Madura stall that has various unique features in terms of accessibility and operating hours. The existence of this stall continues to face challenges in the business world, so that service quality and pricing are important aspects that influence consumer satisfaction and loyalty. This study will test and analyze the effect of service quality and price on loyalty through consumer satisfaction. The type of research is associative causal with a population whose number is not known for sure. The sampling technique was purposive random sampling and the results of the sample calculation were 80 respondents. The data source was primary data and was collected through questionnaires. Furthermore, it was analyzed using SEM-PLS path analysis. The results showed that service quality and price had a direct and significant effect on satisfaction. Service quality and price had no effect, while consumer satisfaction had a direct and significant effect on consumer loyalty. Service quality and price indirectly affected loyalty through consumer satisfaction.